Determination of the Neutron Beam Spatial Profile at n_TOF EAR-2 using the CR-39 Track Detectors - Eleme, Z.; Alexandropoulou, M.; Georgiadou, A.; Ioannides, K. G.; Kokkoris, M.; Patronis, N.; Stamatopoulos, A.; Stamoulis, K. C.; Tsinganis, A.; Vlastou, R.; n_TOF Collaboration, and the (HNPS Advances in Nuclear Physics, 2019)
Within the present work the neutron beam spatial profile was determined at the sample position in EAR-2 at the n_TOF facility at CERN. The CR-39 detectors were coupled with a 2mm PE foil serving as neutron-to-proton converter. Two irradiations were performed in the 10x5 cm surface of CR-39 detectors. Proton tracks were revealed in the CR-39 detectors resulting from the elastic scattering of fast neutrons on the hydrogen atoms in the PE converter. Afterwards, the CR-39 detectors were chemically etched in aqueous NaOH solution and latent tracks were considerably enlarged to become visible under an optical microscope. After the scanning of the detectors surface, the acquired images were analyzed using the ImageJ program. In the present work, the experimental setup and procedure will be presented along with the results concerning the characterization of the neutron beam spatial profile at the sample position in the n_TOF EAR-2.